P227 A novel ct scoring system differentiates admissions secondary to eosinophilic from non-eosinophilic asthma. (15th November 2017) - Hynes, G; Tsakok, M; Shrimanker, R; Bradicich, M; St Noble, V; Gleeson, F; Pavord, I
Abstract : Introduction: Post-mortem studies of patients who have died from asthma show that mucus plugging of the airways is a prominent feature. We have investigated whether this can be identified and quantified on CT scans taken at the time of a severe asthma attack and tested the hypothesis that mucus plugging is specific to attacks associated with a raised blood eosinophil count. Methods: We developed a scoring system based on features on CT scans of asthmatic patients potentially associated with mucus plugging (see Table 1 ). We used this scoring system to retrospectively score CT scans of 6 patients admitted to the John Radcliffe Hospital, Oxford, with acute attacks of asthma. CT scans were performed within three days of admission to investigate whether there was an alternative cause for the patients' presenting symptoms. Two radiologists, blinded to clinical measures for the patients, independently scored the CT scans. Results: Four patients had a blood eosinophil count ≥0.3 × 10 9 /litre at the time of admission. The mean (range) CT score was 18 (17) in these patients and 6 (4) in the non-eosinophilic patients. The intraclass correlation coefficient between the two radiologists' scores was 0.823. The largest contributors to the difference between the eosinophilic and non-eosinophilic patients' scores was bronchial wall thickening (6 v 1) and mucus plugging (3 v 0). Conclusion: Our scoring system was repeatable between observers and might potentially identify a pathophysiological mechanism particularly associated with eosinophilic asthma attacks.